Expanding Notions of Culture and Ethics in Health and Medicine to Include Marginalized Groups: A Critical Perspective - Stephenson, Peter H. (Anthropologica, 2022)
I am concerned with the manner in which an almost exclusive focus on the individual has been part of a more general process that increasingly marginalizes the most vulnerable people. A highly individual view of what constitutes the realm of ethics stems both from the cultural value of extreme individualism expressed in the industrialized west and a narrow conceptualization of culture itself. I will argue that this has profound consequences not just for groups like minorities and the poor, but also ultimately for our species itself. This is because a failure to attach ethical discussions to groups cannot adequately critique ecological disasters. Ultimately, it is our species that is threatened by a medical ethics narrowly bound to the notion of individual rights rather than to ideas of responsibility and human rights. I will illustrate this with examples drawn from the evolution of increasingly virulent diseases created largely by the pharmaceutical industry and the obsessive quest for individual longevity via organ transplantation that has led to a profound misunderstanding of cancer.